The effect of uremic toxins to rabbit thoracic aorta and Labeling with technetium-99m - Kara, G (Springer, 2004)
[Abstract Not Available]
17th Annual Congress of the European-Association-of-Nuclear-Medicine -- SEP 04-08, 2004 -- Helsinki, FINLAND